Family-Based Justice in the Sentencing of Domestic Violence - Dinovitzer, Ronit (The British journal of criminology, 2007)
While historical research has noted the importance of the family' in criminal justice, recent empirical work has tended to neglect the emphasis placed on the family in the criminal process. Drawing on Daly's work on familial justice, this paper investigates the role of the family in the sentencing of offenders in a specialized domestic violence court. We examine both the likelihood of incarceration and the determinants of sentence length, and find that conceptions of the family continue to have an important influence on these criminal process outcomes. In cases in which the victim has suffered serious injuries, offenders in intact relationships are more likely to be sentenced to jail, yet, at the same time, when incarcerated, these offenders receive shorter sentences. Thus, even as researchers are documenting broader shifts away from the promotion of substantive values through the criminal process, the current study suggests the continued relevance of family-based justice' in the sanctioning of offenders, so that moral imperatives continue to intersect with the actuarial logic of modern penal practices